Experimental Investigation On Tribological Properties Of Natural Oil-Based Lubricants As Sustainable Bio-Lubricants - Md Jasman, Md Eirfan Safwan (2018)
Nowadays the depleting of crude oil become an escalated global issue.Bio-based lubricant is seen as the alternative to the conventional petroleum based lubricant.The similarities between the properties of bio-based lubricant with conventional lubricant and greener system of bio-based lubricant are the strong point of bio based lubricant.This work investigates the tribological properties of natural oil-based lubricants and prospects of Hexagonal Boron Nitride (hBN) as additive for the lubricants in order to find a suitable alternative to the conventional lubricant.hBN is considered as a good candidate among other nanoparticles for the lubricant additives due to their roller-like shape,polishing property,extremely small particle size and unique mechanical properties.The experiment is conducted to obtain the friction and wear characteristics by using four-ball tester set-up.Based on the result,the pure bio-based lubricant shows better anti-wear property and lower value of coefficient of friction (COF).By adding 0.01wt% hBN additive to the bio-based lubricant,the wear scar for the bio-based lubricant is reduced by 99%.For refine glycerin (RG) the COF value is reduced significantly with the present of the additive but the oleic methyl ester (OME) has the opposite effect.